The Effect of Electronic Customer Relationship Management on Organizational Performance with Mediating Role of Customer Satisfaction - Hanif, Muhammad Imran; Ahsan, Muhammad; Bhatti, Muhammad Kashif; Loghari, Muhammad Sajjad (International Review of Management and Marketing, 2020)
The purpose of this paper is to measure the effect of E-CRM on Organizations Performance. The Information technology plays an important role in every organization. And customer satisfaction needs to also be measured as a mediator to judge the efficiency. The research was conducted by randomly sampling method in Pakistan. The Methods were used Qualitative and Quantitative for Research. A sample of 220 questionnaires was developed and interview was conducted to get response, through a well-organized strategy. How Technology Effect the customers and it gives a perceiving effect on businesses. The interviews were conducted from Managers of different banks. Our findings were related with positive impact on the organization practices to evaluate the effectiveness. This shows that the effect of electronic customer relationship is positively associated with organization because due to increase in competition it is compulsory for organization to maintain the ECRM. Our finding is E-CRM has an important effect on organization and its customers. This model has a practical implication on services based industry organizations. The firm would use the ECRM system to increase the efficiency of employees and retention rate of customer will increase. Keywords: Electronic Customer Relationship Management: Organizational Performance: Customer Satisfaction JEL Classifications: M310; M1; M0 DOI: https://doi.org/10.32479/irmm.9934